S. cerevisiae ERG5DeltaNTH1DeltaAMS1Delta construction enhancing stress tolerance for ethanol production increase in the presence of inhibitors and mechanism analysis based on the comparative transcriptomics - Peizhou Yang; Zhuanzhuan Lin; Jianchao Chen; Shuying Jiang; Zhi Zheng; Kanglin Wang (Heliyon)
Saccharomyces cerevisiae is considered the most promising large-scale production strain with ethanol as the main product. The fermentation of Saccharomyces cerevisiae is generally inhibited under various stress conditions. Various inhibitors in the hydrolysate severely inhibit yeast proliferation and yeast accumulation. In this study, S. cerevisiae ERG5, NTH1, and AMS1 were knocked out to improve the yeast stress tolerance by the Clustered Regularly Interspaced Short Palindromic Repeats Cas9 (CRISPR-Cas9) technology. The result indicated that the stress tolerance of S. cerevisiae ERG5ΔNTH1ΔAMS1Δ mutant (S. cerevisiae SCENA) was remarkably improved compared with the wild-type strain. The contents of fecosterol, trehalose, and mannan in S. cerevisiae SCENA were 1.67, 1.53, and 1.47 folds compared with those in the control. The ethanol concentration in S. cerevisiae SCENA reached 16.5 g/L, which was 1.23 folds compared with the control using rice bran hydrolysate. Further, the transcriptome analysis indicated down-regulated differential expression genes (DEGs) in S. cerevisiae SCENA were mainly from cellular response to glucose, cell periphery, and plasma membrane. Up-regulated DEGs were mainly from spore wall assembly, fungal-type cell wall assembly, and ascospore wall assembly. Thus, S. cerevisiae SCENA could effectively produce ethanol using the fermentation of lignocellulosic hydrolysate in the presence of inhibitors by regulating fecosterol, trehalose, and mannan metabolisms.